Radiological diagnosis of infantile osteopetrosis in a 1-year-old with macrocephaly and jaundice - Aya Laridi, MD; Chaimaa Jabbari, MD; Ihssane Laasri, MD; Soufiane Hassar, MD; Nazik Allali, PhD; Latifa Chat, PhD; Siham El Haddad, PhD (Radiology Case Reports, 2025)
Infantile osteopetrosis is a rare, severe genetic disorder marked by defective osteoclast function, leading to abnormally dense but fragile bones. Early diagnosis through radiologic imaging is essential for proper management, as it often reveals hallmark features such as diffuse skeletal sclerosis, the “bone-in-bone” appearance, and the “Harlequin mask” appearance. We present the case of a 1-year-old female who presented with macrocephaly, jaundice, and hepatosplenomegaly, alongside a family history of similar symptoms with sibling deaths. Clinical examination revealed dysmorphic facial features, growth retardation, and hematologic abnormalities including severe anemia and thrombocytopenia. Brain CT imaging demonstrated triventricular hydrocephalus, while skull X-rays revealed characteristic radiologic signs of osteopetrosis, including the “Harlequin mask” appearance and “sandwich” vertebrae. The diagnosis was confirmed based on these clinico-radiologic findings, given the unavailability of genetic testing. Osteopetrosis, particularly the autosomal recessive form, poses significant risks including bone marrow failure, fractures, and cranial nerve compression. This case underscores the critical role of radiologic evaluation in early detection and timely intervention, such as hematopoietic stem cell transplantation (HSCT), which may improve long-term outcomes. Our report highlights the importance of radiologic findings in diagnosing and managing this rare and potentially life-threatening condition.